Pseudocapacitance of α-CoMoO4 nanoflakes in non-aqueous electrolyte and its bi-functional electro catalytic activity for methanol oxidation. (14th December 2015) - Padmanathan, N.; Shao, Han; Selladurai, S.; Glynn, Colm; O'Dwyer, Colm; Razeeb, Kafil M.
Abstract: Nanocrystalline cobalt molybdate (CoMoO4 ) nanoflakes were grown directly on carbon fibre cloth (CFC) via a simple hydrothermal method without any template or surfactant. A symmetric supercapacitor was fabricated using CoMoO4 nanoflakes/CFC as both negative and positive electrodes. The device has delivered the maximum specific capacitance of 8.3 F g −1  at a constant current density of 1 A g −1 in organic electrolyte. It offers the reasonable energy (2.6 Wh kg −1 ) and power density (748.8 W kg −1 ) as comparable to the carbon based symmetric supercapacitors. As a catalyst for methanol oxidation, the CoMoO4 nanoflakes showed high current density (25 mA cm −2 ) and low onset potential (0.38 V). The impressive bi-functional electrochemical activity of CoMoO4 on CFC is mainly attributed to its porous microstructure, where reasonable electrical conductivity resulted from binder-free and intimate metal oxide/substrate integration. Highlights: α-CoMoO4 nanoflakes was prepared via single-step hydrothermal approach. The materials was tested as a bi-functional electrode for supercapacitor and DMFC. A symmetric supercapacitor was investigated in 1 M TEABF4 /PC and 3 M KOH electrolytes. Electro-oxidation of methanol was studied in alkaline medium.